Distribution, biological effects and biofilms of microplastics in freshwater systems - A review. (July 2022) - Wang, Yan; Zhou, Beihai; Chen, Huilun; Yuan, Rongfang; Wang, Fei
Abstract: The rapidly rising output and mass use of plastics have made plastics pollution a major environmental problem. Since plastics are persistent in the environment, understanding the migration transformation characteristics of plastics is critical. Given the ever-increasing concern about the environmental risks posed by microplastics, their prevalence, fate, abundance and impact have been intensively studied. Most of these investigations focused on the marine environment, but research on freshwater microplastics is less extensive. This article aims to briefly summarize the research progress of freshwater microplastics, identify existing gaps and draw novel conclusions, so as to provide useful information for the research of freshwater microplastics. Using the statistics and analysis of freshwater microplastics studies in 2016–2021, this review systematically discusses microplastics in globally freshwater systems. The biological effects of microplastics on freshwater organisms were discussed as well. Some potential ecological effects of microplastic biofilms were shown, such as climate change and material circulation. More importantly, we present some unique conclusions. For example, the detection of freshwater microplastics is mainly concentrated in natural freshwater systems, while few are concentrated in artificial freshwater systems. In addition, polystyrene is the main mode for testing the biological effects of freshwater microplastics, and polyethene and polypropylene which are the most common in freshwater environments, have not been taken seriously. We also pointed out that studies on advanced freshwater plants in the topic of biological effects of microplastics still need strengthen. Graphical abstract: Image 1 Highlights: Freshwater microplastics are distributed all over the world. Biological effects of microplastics are affected by many factors. Microplastic biofilms can produce complex ecological effects. There are still many gaps in freshwater microplastics research.